Mathematics Fun Day for Orphanage of Pemerhati dan Penguatan Anak Negeri Kota Langsa - Rizki - Amalia (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2018)
The aim of this Community Service is to give motivation of study and basic knowledge of counting in mathematics and its application. The target of this service is children in orphanage of Pemerhati dan Penguatan Anak Negeri Kota Langsa. This service using direct approach method, speech, and practical activities. The approach method is performed with problem observation which is faced by chidren in the  orphanage related to mathematics learning. Presentations about how to do quick and right count are performed in each group of elementary school (SD), junior high school (SMP) and senior high school (SMA) as well as its games in order to find the first rank of these group. This Service got a great response from the children. The observation of this community service’s implementation can be concluded as: (a) The level of partisipation from our mitra for this community service “Mathemtics Fun Day” gives possitive affect for this community service and (b) The programm implementation of this service is able to improve knowledge and learning motivation in mathematics, especially in algebra operation. Therefore, this program is useful to increase the grade of mathematics subject in their school.